Pixel value graphical password scheme: k-means as graphical password fault tolerance - Mohd Afizi Mohd Shukran (Tanjung Malim, 2021)
Pixel value graphical password scheme: k-means as graphical password fault tolerance by Mohd Afizi Mohd Shukran